Effects of clouds on the surface shortwave radiation at a rural inland mid-latitude site - Salgueiro, Vanda (2017)
Seven years (2003–2010) of measured shortwave (SW) irradiances were used to obtain estimates of the 10 min averaged effective cloud optical thickness (ECOT) and of the shortwave cloud radiative effect (CRESW) at the surface in a mid-latitude site (Évora — south of Portugal), and its seasonal variability is presented. The ECOT, obtained using transmittance measurements at 415 nm, was compared with the correspondent MODIS cloud optical thickness (MODIS COT) for non-precipitating water clouds and cloud fractions higher than 0.25. This comparison showed that the ECOT represents well the cloud optical thickness over the study area. The CRESW, determined for two SW broadband ranges (300–1100 nm; 285–2800 nm), was normalized (NCRESW) and related with the obtained ECOT. A logarithmic relation between NCRESW and ECOT was found for both SW ranges, presenting lower dispersion for overcast-sky situations than for partially cloudy-sky situations. The NCRESW efficiency (NCRESW per unit of ECOT) was also related with the ECOT for overcast-sky conditions. The relation found is parameterized by a power law function showing that NCRESW efficiency decreases as the ECOT increases, approaching one for ECOT values higher than about 50.